Factors Influencing Outsourcing Services in Iranian Medical Centers: A Systematic Review - omid khosravizadeh; Mohammad Zakaria Kiaei; Saeed Shahsavari; Nasibeh Mansouran Tazekand (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Identifying the key factors effective on outsourcing can play a significant role in helping healthcare decision makers to present solutions to improve the outsourcing situation. This study was conducted in order to systematically review the factors influencing the decision making to outsource the services of Iranian medical centers. Methods: Data was collected through searching for keywords in Google Scholar, PubMed, Scopus, Web of Science, Science direct, Magiran, SID and Irandoc databases from January 2010 to December 2020. Also, the quality of the studies was measured and verified by three experts utilizing the Strobe checklist. Researchers classified results achieved by the study. Results: 10 articles were selected that responded to the studychr('39')s questions. 44 components in seven dimensions including (economic and financial components, components of laws and regulations (legal), components of supervision and control, components of service type, components of executive capability of the organization, components of the external environment of the organization and components human resources) were recognized on the decision to outsource services in medical centers in Iran. Conclusion: Policy makers at the decision-making level and managers at the executive level should consider the efficient components and dimensions before deciding to execute outsourcing in units according to the wanted structure, process and consequences, and then make the needed decision regarding the implementation.